Asymmetric effects of housing wealth on consumption: Malaysia case - Wang, Li; Wong, Kelly Kai Seng; Tee, Chee Lip (Elsevier, 2019)
This paper aims to test the asymmetric effect of housing wealth on consumption in Malaysia. The nonlinear model is tested by Unrestricted Autoregressive Distributed Lag (ARDL) proposed by Shin et al. (2011). This study found that income, credit constraints, stock wealth and housing wealth are cointegrated. The estimated model shows that there are asymmetric relations between housing wealth and consumption.